Ofertam-se serviços: anúncios de professores no jornal O Publicador (1864-1885), na província da Paraíba - Araújo, Camila Almeida de (2015)
The objective of the present research is to analyze the means of representation of teachers in service offer advertisements published in the O Publicador newspaper (1864 - 1886), in the Paraíba Province, by means of a corpus consisting of 21 advertisements. This genre of speech was a representation of one of the means for manifesting experiences propagated throughout society, amongst social, economic and educational issues, by which it is possible to observe the various forms of expression of a given period. The theoretical and methodological premise adopted in this research states under the New History’s perspective, basing itself in historical research. This research called upon the contributions that came from Michel Foucaults’s, Michel de Certeau’s and Roger Chartier’s works as its theoretical supports. The authors were chosen due to the manner they discourse about text and speech. Their works facilitates the comprehension about the representation of teachers in service offer advertisements, as their speech covers the following concepts: enunciation, speech and speech formation. This research is bootstrapped by the analysis of written sources, contemplating the following thematic categories: Instruments classes, vocal or piano, Latin, French, English, first letters, and sewing, embroidery or fixes. The figure of the teacher in the O Publicador newspaper’s advertisements is to be understood as a representation of reality and, as such, being a way of identifying the social space of this subject, who would publish in the newspapers’ pages. Beyond the advertisements, it is also possible to extrapolate the figure of the teacher by searching evidence left throughout legislation, reports of provincial presidents and congener researches, basing itself on the contradictory relationships of society. The discourse offered by the teachers, by means of the advertisements, expose one of the ways these professionals had to demonstrate their status position in the imperial society. Such position is marked by an order in the discourse, in which whatever was written in the pages of the newspapers was all that could be said, since they were immersed in a disciplinary society, moved by rules that would determine the behavior of the subjects. The teacher frequently appears as an announcer, especially offering their services but not limited to this utility. Yet, they resorted to other methods of laying evidence on how their profession was configured, by selling books, warnings on changing class locations and warning that they have moved from being a private teacher to become a public teacher. So, it becomes evident the mobility of these subjectsin their social space, taking basis in the material evidence of the advertisements, by allowing a visualization of an educational legacy and their role in the context of the imperial Brazil. There for, the representation the teachers reveal with their practices, in this case with the advertisements, displays a multiplicity of aspects destined to the private teaching, in order to pull attention to their offerings, by their civil state, their anonymity, by being a disciple or by being the owner of a school. Thus expressing their dispersion amongst the regularities of their speech, or also, the necessity to offer their service.